Iraq Stock Exchange Performance Determinants: A literature review - Marane, Bayar (Technium Social Sciences Journal, 2022)
Financial markets have a significant role in economic development; Iraq's stock exchange trades and mobilize financial resources as the only stock market operating in Iraq. All statistics indicate the progress of the Iraq stock exchange compared to the previous period, especially before the lockdown due to covid in (2019). However, the Iraqi stock exchange capitalization still did not get to one percent of the total capitalization of the entire Arab financial markets. Furthermore, past studies' results concluded that there is still no consistent or inconclusive relationship between the macroeconomics variables and the Iraq stock exchange performance. Therefore, Iraq is still a solid context to explore the linkage between these variables, mainly due to Iraq's economy as one of the economies having substantial oil reserves in the MENA region. Also, the Iraq stock exchange needs to activate all ways to make the information available or access information by all investors to make the Iraqi stock exchange efficient to prevent the possibility of achieving abnormal profits by some investors.